The Eastern Canadian Arctic at ca. 6 ka BP: A Time of Transition - Williams, Kerstin; Short, Susan; Andrews, John; Jennings, Anne; Mode, William; Syvitski, James (Géographie physique et Quaternaire, 1995)
ABSTRACTThe middle Holocene was a time of definite environmental transition in the Eastern Canadian Arctic. Based on several proxy indicators (pollen, diatoms, foraminifera, molluscs and nearshore sedimentation rates), it appears that a thermal maximum occurred around middle Holocene (6-4 ka), several thousand years after the insolation maximum — a lag caused by the thermal inertia of the earlier massive ice sheet. Terrestrial records indicate that a warming began around 6 ka, both in the subarctic (Labrador - Ungava) and on Baffin Island. Marine records, on the other hand, suggested major water structure changes around 6 ka both in the Northeastern Canadian Arctic and also along the East Greenland coast with evidence of a marine surface water temperature maximum at 8 ka. We hypothesize that the marine circulation changes, both along the Baffin Island and along the East Greenland coasts, were primarily driven by glacio-isostatic uplift of the Arctic Channels. With the cessation of water flow of Atlantic (warmer) origin, and decrease in water volume from the deeper parts of the Arctic Ocean through the Arctic Channels, the export through the Fram and Denmark straits increased and the water column changed. Changes in the concentration and duration of sea ice along the eastern Canadian coast would have had important repercussions on the biota of the coastal marine and terrestrial ecosystems.